How organizational identity relates to knowledge sharing and creativity: moderating effect of perceived organizational support - Imamoglu, Salih Zeki; Erat, Serhat; Turkcan, Hulya (Emerald Group Publishing Ltd, 2023)
Purpose This study aims to broaden the current literature by examining the relationships between organizational identity, knowledge sharing and creativity with moderating role of perceived organizational support. Design/methodology/approach Data were collected from 291 teachers working in vocational high schools by using a survey method. After data collection, construct validity and reliability were assessed and direct relationships were examined by using structural equation modeling (SEM). In addition, a hierarchical moderated regression analysis was conducted. Findings It was found that (1) organizational identity is positively related to knowledge sharing, (2) organizational identity is positively associated with creativity, (3) knowledge sharing does not mediate the relationship between organizational identity and creativity and (4) perceived organizational support positively moderates the relationship between organizational identity and knowledge sharing whereas it does not moderate the relationship between organizational identity and creativity. Originality/value Drawing on social identity theory (SIT) by integrating social exchange theory (SET), this research broadens the current literature by empirically showing the untapped effects of organizational identity on knowledge sharing and creativity and the role of perceived organizational support as a moderator on these relationships. This study confirms the effect of organizational identity on creativity and knowledge sharing. In addition, this research is the first that investigates the moderating role of perceived organizational support on the effect of organizational identity on knowledge sharing and creativity. Therefore, this study provides a deep understanding of these relationships and contributes to the literature.
Keywords: Organizational identity; Knowledge sharing; Creativity; Perceived organizational support